PENGARUH PEMBERIAN PUPUK KANDANG DAN PUPUK N, P DAN K TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Supariadi Supariadi; Husna Yetti; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the interaction of organic manure and N, P and K fertilizeron the growth and production of onion as well as getting the best dosage. This research has been carried out in the garden Experimental Faculty of Agriculture, University of Riau from March to May 2016. The study consists of two factors, the first factor that manure with a dosage of 10 ton/ha, 20 ton/ha and 30 ton/ha. The second factor is urea, TSP and KCl which consists of three levels without treatment Urea, TSP and KCl, 1/4 the recommended dosage, Urea 125 kg/ha + TSP 50 kg/ha + KCl 50 kg/ha and 1/2 recommended dosage, Urea 250 kg/ha + TSP 100 kg/ha + KCl 100 kg/ha, which is arranged in a randomized block design (RAK). From these two factors obtained 9 treatment combinations, each treatment was repeated 4 times, thus obtained 36 experimental units. Observation Data were statistically analyzed using ANOVA, the results of variance followed by using Duncan's multiple range test at 5% level. The parameters measured were the number of leaves, number of tubers per hill, convolution bulb, tuber fresh weight per plant, tuber fresh weight per plot and weights shelf per plot. Data results shows that the best results using cow manure dosage of 30 ton/ha and urea 250 kg/ha, TSP 100 kg/ha, KCl 100 kg/ha.Keywords: Onion, Cow Manure, Fertilizer TSP and KCl